Pendidikan Islam dan Critical Pedagogy Paulo Freire: Upaya Pemberantasan Korupsi Sistemik: Islamic Education and Paulo Freire's Critical Pedagogy: Efforts to Eradiate Systemic Corruption - Nurli Nurlinda; Fadeli; Mohamad Ali (Prodi PAI, Fakultas Tarbiyah, UNIDA GONTORs Tarbiyah, Universitas Darussalam Gontor, 2025)
Corruption in Indonesia is believed to have become an entrenched part of the social structure. Indonesia Corruption Watch reported that the number of corruption cases throughout 2023 reached the highest level in the past five years, with potential state losses amounting to IDR 28.4 trillion. Corruption damages the values of integrity and national identity, leading to a systematic decline in the quality of human behavior if left unaddressed. Efforts within the field of Islamic education have been carried out through character education aimed at shaping individuals who reject corruption. However, individual-based efforts alone are insufficient to eradicate systemic corruption. This study develops an anti-corruption education approach that not only cultivates individual morality but also promotes collective movements against corruption through the integration of Paulo Freire’s Critical Pedagogy theory with Islamic education. This study employs a qualitative method with descriptive, interpretative, and conceptual analytical approaches. The relationship between corruption, social structure, and the role of Islamic education is analyzed descriptively. Interpretative and conceptual analyses are conducted on Paulo Freire’s Critical Pedagogy theory and the values of Islamic education derived from the Qur’an and Hadith to formulate an anti-corruption education concept relevant to the Indonesian context.